Recent Publications (Quarterly Journal of Economics, 1955)
Recent Publications The Quarterly Journal of Economics, Volume 69, Issue 2, May 1955, Pages 318–320, https://doi.org/10.1093/qje/69.2.318 Published: 01 May 1955